CEO ACTIVISM AND SUPPLY CHAIN INTERACTIONS. (8th February 2018) - HINTERECKER, Harald; KOPEL, Michael; RESSI, Anna
ABSTRACT: In this paper we demonstrate that hiring a manager with a propensity to over‐invest in socially and environmentally responsible production can increase firm profits if customers not only care about the responsible behavior of the market firm but also about the engagements of all players along the firm's supply chain. The new mechanism we identify relies on the complementarity of investments by the firm and its suppliers. We demonstrate that CEO activism of this kind might cause a win‐win outcome where all parties along the supply chain, the firm's customers and society can be better off.